Performance Evaluation of Recycled Coarse Aggregate in Self-Compacting Concrete - Bajracharya, Matina; Kunwar, Sanjaya; Praveen, Kannam (Journal of Engineering Issues and Solutions, 2025)
This study evaluates the performance of Recycled Coarse Aggregate (RCA) in Self-Compacting Concrete (SCC) as a sustainable alternative to natural coarse aggregate (NCA). SCC mixes of M30 and M50 grades were prepared with RCA replacing NCA at 0%, 20%, 40%, 60%, 80%, and 100%. Basic material properties were examined through standard tests including sieve analysis, specific gravity, and aggregate strength indices. Fresh concrete properties were evaluated using the slump flow and V-funnel tests, while mechanical properties were assessed via compressive and split tensile strength tests. Results showed that up to 40% RCA replacement had negligible effects on workability, with mixes exhibiting excellent flow and no segregation. However, mechanical strength declined with increasing RCA content. Notably, 20% RCA in M50 mixes retained target compressive strength, whereas M30 mixes with the same replacement fell short. SEM analysis at 20% RCA revealed minimal changes in the Interfacial Transition Zone (ITZ), indicating a stable microstructure. Durability evaluation through acid attack tests revealed minimal differences in mass and strength loss between conventional and 20% RCA-replaced SCC.